A Thanksgiving drawing feast! - Besel, Jennifer M; Makuc, Lucy (North Mankato, Minnesota Capstone Press, 2014)
"Step-by-step instructions and sketches show how to draw common Thanksgiving and autumn images and symbols"--Provided by publisher
Drawing
Includes bibliographical references
Keywords: Autumn in art -- Juvenile literature; Drawing -- Technique -- Juvenile literature; Thanksgiving Day in art -- Juvenile literature